Identifikasi Endoparasit pada Feses Lembu (Bos taurus) di Desa Tuntungan 2 Kecamatan Pancur Batu Deli Serdang Provinsi Sumatera Utara - Augustin Ningrum, Nurlian; Wahyuni, Rana; Aulia Puspita, Rizka; Aprilia, Lola; Aulia Pohan, Dinda (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
Various types of diseases can occur on farms. One of the diseases in livestock is caused by infection with parasites and parasitic worm eggs. This parasite can attack the stomach organ tissue in cattle and can even spread to other organ tissue such as the liver, lungs, and even the brain. The aim of this research was to identify various types of parasites and estimate their occurrence in cow dung in Tuntungan 2 Village, Pancur Batu District, Deli Serdang Regency, North Sumatra Province. Twenty samples of cow dung were used. Sampling was carried out randomly, by collecting 10 grams of feces at each location. Floating, Sedimentation, and Mc Master methods are used in the identification process. apply parasite prevalence models to data analysis calculations. Research findings show that parasitic worms are found in animal feces in Tuntungan 2 Village. There are 3 types of worms found, namely: Trichostrongylus sp. Bunostomum sp and Oesophagostum sp. Meanwhile, 4 types of worm eggs were found, namely Eimeria sp, Oesophagostum sp, Bunostomum sp, and Trichostrongylus sp. T1 sample location is 0.45% which is more dominant. The prevalence of infection is quite high. With the degree of infection of all species in the heavy category, the degree of infection was most often found at the T1 sample location which had a very high number of parasitic worm eggs.